2016
DOI: 10.5897/jvmah2015.0465
|View full text |Cite
|
Sign up to set email alerts
|

Major causes of lung and liver condemnation and associated risk factors in cattle slaughtered at Hawassa Municipal abattoir, Southern Ethiopia

Abstract: The study was conducted from November, 2013 to March, 2014 at Hawassa municipal abattoir, Southern Ethiopia with the aim of identifying the major causes of liver and lung condemnation and assessing possible risk factors associated with organ condemnation. Standard ante-mortem and post-mortem procedures were followed throughout the study and abnormalities were recorded. A total of 399 cattle were considered for ante mortem and post-mortem examination by systematic random sampling technique. In ante mortem inspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Most of the animals slaughtered in the abattoir were come from farta breed of cattle, which are low cost than Bahir dar cattle which come from distant area (around este and Debretabor). In this study period the prevalence was greater than that of the reported in the country and elsewhere Africa, like Fasciolosis in Slaughtered Cattle in Addis Ababa Abattoir, Ethiopia was 23% [23], from northern Ethiopia who reported 24.3%, [9] recorded, a prevalence of 46.2% at Jimma abattoir, (24) from Zambia and [24] from Zimbabwe reported 53.9% and 31.7% prevalence respectively. On the other hand a lower prevalence of fasciolosis (14.0%) has been observed in slaughter cattle at Wolaita Soddo abattoir [10].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Most of the animals slaughtered in the abattoir were come from farta breed of cattle, which are low cost than Bahir dar cattle which come from distant area (around este and Debretabor). In this study period the prevalence was greater than that of the reported in the country and elsewhere Africa, like Fasciolosis in Slaughtered Cattle in Addis Ababa Abattoir, Ethiopia was 23% [23], from northern Ethiopia who reported 24.3%, [9] recorded, a prevalence of 46.2% at Jimma abattoir, (24) from Zambia and [24] from Zimbabwe reported 53.9% and 31.7% prevalence respectively. On the other hand a lower prevalence of fasciolosis (14.0%) has been observed in slaughter cattle at Wolaita Soddo abattoir [10].…”
Section: Discussionmentioning
confidence: 71%
“…The finding of mixed infection with the two species of Fasciola indicates that there are places in the region where the climato-ecological conditions favour the existence of the intermediate snail hosts for both species. Several studies in other Africa countries, however, showed that F. hepatica is the predominant [24], [26], [27], [28][29]. There was a statistically significant association (P <0.05) between Fasciola prevalence and body condition of the animals.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation